Assessing the validity of random blood glucose testing for monitoring glycemic control and predicting HbA1c values in type 2 diabetics at Karl Bremer hospital - Daramola, Oyekemi Funke (Stellenbosch : Stellenbosch University, 2013)
Thesis (MMED)--Stellenbosch University, 2012.